Investigation of time-resolved proton radiography using x-ray flat-panel imaging system. (9th February 2017) - Jee, K-W; Zhang, R; Bentefour, E H; Doolan, P J; Cascio, E; Sharp, G; Flanz, J; Lu, H-M
Abstract: Proton beam therapy benefits from the Bragg peak and delivers highly conformal dose distributions. However, the location of the end-of-range is subject to uncertainties related to the accuracy of the relative proton stopping power estimates and thereby the water-equivalent path length (WEPL) along the beam. To remedy the range uncertainty, an in vivo measurement of the WEPL through the patient, i.e. a proton-range radiograph, is highly desirable. Towards that goal, we have explored a novel method of proton radiography based on the time-resolved dose measured by a flat panel imager (FPI). A 226 MeV pencil beam and a custom-designed range modulator wheel (MW) were used to create a time-varying broad beam. The proton imaging technique used exploits this time dependency by looking at the dose rate at the imager as a function of time. This dose rate function (DRF) has a unique time-varying dose pattern at each depth of penetration. A relatively slow rotation of the MW (0.2 revolutions per second) and a fast image acquisition (30 frames per second, ~33 ms sampling) provided a sufficient temporal resolution for each DRF. Along with the high output of the CsI:Tl scintillator, imaging with pixel binning (2  ×  2) generated high signal-to-noise data at a very low radiation dose (~0.1 cGy). Proton radiographs of a head phantom and a Gammex CT calibration phantom were taken with various configurations. The results of the phantom measurements show that the FPI can generate low noise and high spatial resolution proton radiographs. The WEPL values of the CT tissue surrogate inserts show that the measured relative stopping powers are accurate to ~2%. The panel did not show any noticeable radiation damage after the accumulative dose of approximately 3831 cGy. In summary, we have successfully demonstrated a highly practical method of generating proton radiography using an x-ray flat panel imager.